Reversed halo sign: from a clinico-radiologic–pathologic point of view - Yuan Ye; Run Zhang; Kaiyue Diao; Hua Zhou; Xuanli Xu; Liangjie Fang; Apoorva Sinha; Lingfang Tu; Jianya Zhou (European Journal of Medical Research)
Abstract Reversed halo sign (RHS) is characterized by a central ground-glass opacity surrounded by a crescentic or ring-shaped consolidation. It was originally described as a pathognomonic imaging feature of cryptogenic organizing pneumonia (COP), but has subsequently been observed in a wide variety of pulmonary disorders, including infectious and non-infectious diseases. Although RHS is currently considered as a non-specific and non-pathognomonic sign, a careful analysis of its radiologic characteristics together with clinical features can greatly facilitate the differential diagnosis. The paper presents a state-of-the-art review of RHS, we retrospectively review the definition of RHS in chronological order and comprehensively summarize the spectrum of pulmonary diseases associated with RHS. In addition, the radiologic–pathologic correlations of RHS in different disease entities are systemically discussed and an integrated approach is proposed to establish the differential diagnosis of RHS.